Tradição e transformação no Pampa Serrano das Guaritas do Camaquã: um estudo de percepção da paisagem - Souza, Luiz Paulo Martins e (2018)
The following research is a case study on landscape perception. The central scope was to investigate the levels of identification of the ranchers of the Guaritas do Camaquã area with the traditions and transformations that are taking place in the traditional landscapes of southern Brazilian pampean grasslands. In order to reach its goals, this research used the methodological procedure “photo-test”, followed by interview; the photo-test relies on the evaluation of photographs representing scenes from different landscapes. These landscapes were organized into different categories of preference. In general, the data produced by the research evidence the high degree of identification of the population involved with the preference categories “hilly grasslands”, “cattle breeding and management” and “unpaved roads”. On the other hand, the categories “forestry” and “urban life” were some of the categories that received the lowest grades by the population of ranchers. There are also significant differences between the evaluations performed by men and women.